Rugby Union contact skills alter evasive agility performance during attacking ball carries - Wheeler, K. W.; Sayers, M. G. L. (International Journal of Sports Science and Coaching, 2011)
Rugby union is a collision sport where evasive agility running patterns and the tackle contest determine the effectiveness of attacking ball carries. This study used three-dimensional kinematic analysis to examine the running technique of eight highly trained rugby union players during three rugby based reactive (in response to a defender positioned at the side-step) agility conditions (non-contact, contact and fend). The fend condition involved pushing a defender away with the upper body during the side-step and both fend and contact conditions required impact with an additional defender at the straighten-step, simulating a rugby tackle. Results demonstrated that a reduction in the relative height of the centre of mass relative to standing height (%CM) occurred at the straighten-step during the contact condition (47.2 ±1.9 %CM) compared to the noncontact condition (49.1 ±1.8 %CM, p <.001). The fend condition was then shown to increase %CM at the straighten-step (48.4 ±2.7 %CM) when compared to the contact condition (47.2 ±1.9 %CM, p = .017). However this difference was not observed at tackle impact during the straighten-step, with similar %CM values for fend (45.1 ±3.4 %CM) and contact conditions (44.6 ±2.6 %CM, p = .205). Further analysis showed that the number of steps displayed between the side-step and straighten-step (transition phase) altered the %CM, with one step during the transition phase increasing %CM (49.3 ±1.5 %CM) compared to two transition phase steps (46.9 ±1.6 %CM, p < .001) and no transition phase steps (46.5 ±1.6 %CM, p < .001). The changes to running technique during agility conditions involving tackle situations highlight the need for running programs in rugby union to meet the specific requirements of match-play activities.